How does natural gas consumption affect human health? Empirical evidence from China. (20th October 2021) - Zhang, Ruining; Li, Hui; Chen, Tianqi; Hou, Bingdong
Abstract: The Chinese government has taken effective measure to improve the health of residents and build a healthy China, such as optimizing energy structure and expanding natural gas consumption. Even though a large number of studies have explored the relationship between natural gas consumption and health, few studies have focused on China and ignored heterogeneity analysis. To assess the effects of natural gas consumption on mortality, this study applies a two-way fixed effect model by employing panel data from 30 provinces in China from 2002 to 2018. Moreover, this study analyzes the heterogeneity in health effects of natural gas from the perspective of spatial distribution and energy structure. The results indicate that expanding natural gas consumption can significantly reduce the mortality rate. Specifically, an increase in 1 cubic meter in national per capita gas consumption can reduce mortality by 0.0011‰, which is equivalent to 1540 fewer deaths in 2019. Various regions exhibit different results. Expanding natural gas consumption in Central China and regions with high proportion of coal consumption can reduce mortality significantly. 1 cubic meter increase in per capita natural gas consumption inhibits the mortality in Central China by 0.0048‰, while in areas with high proportion of coal consumption by 0.0027‰. In addition, the relationship between natural gas consumption and mortality is verified as linear. Finally, policy implications are proposed for the Chinese government to accelerate the natural gas development and build a healthy China.